Tomboy ebook A graphic memoir. - Prince, Liz (2014)
A memoir about friendship, gender, bullies, growth, punk rock, and the power of the perfect outfit . . . Growing up, Liz Prince wasn't a girly girl, but she wasn't exactly one of the guys either (as she learned when her little league baseball coach exiled her to the distant outfield). She was somewhere in between. But with the forces of middle school, high school, parents, friendship, and romance pulling her this way and that, the middle wasn't an easy place to be. Tomboy follows award-winning author and artist Liz Prince through her early years and explores—with humor, honesty, and poignancy—what it means to "be a girl." From staunchly refuting "girliness" to the point of misogyny, to discovering through the punk community that your identity is whatever you make of it, Tomboy offers a sometimes hilarious, sometimes heartbreaking account of self-discovery in modern America. "Liz Prince may have been an uncertain, confused kid, but she's a confident and sincerely expressive cartoonist. Tomboy is a funny and relatable look at what every child has to deal with at some point — figuring out who you really are inside, when everyone else only sees what they think you should be on the outside."—Jeffrey Brown, author of Clumsy, Jedi Academy, and Darth Vader and Son "Liz Prince portrays the awkwardness and humiliation of childhood with wonderful (not to mention painful) accuracy. Any kid that picks up this book is going to be privy to secrets most of us don't learn until it's too late, and any adult who reads it will be reminded of an essential truth: that it's okay to be exactly who we want to be, no matter how weird everyone else thinks we are. Tomboy isn't a self help book, but it should be."—Julia Wertz, author of Drinking at the Movies and The Infinite Wait "It's hard to imagine anyone failing to be charmed by this entertaining, clever, and genuinely funny memoir of growing up with gender identity confusion. Even this pretty unconfused regular old dude found plenty to identify with in Liz Prince's story of adolescent bafflement, exploration, and discovery — delivered, like all the best such stories, with a light touch, wry wit, understated irony, and not one iota of preachiness. Meaning: I'm a fan. Go Liz!"—Frank Portman, author of King Dork "Liz Prince tells gender norms to eat dirt. A delightful, thoughtful, and compulsively readable memoir. And an important one."—Ariel Schrag, author of Adam and Potential